1996
DOI: 10.1111/j.1447-0756.1996.tb00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8‐hydroxy‐2‘‐deoxyguanosine (8‐OHdG) Levels in Women with or without Gynecologic Cancer*

Abstract: These results suggest that it might be possible to determine the spread of cancer to some extent by determining a patient's urinary 8-OHdG level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 7 publications
2
32
0
1
Order By: Relevance
“…In an epidemiological study, Kasai et al reported that when subjects were divided into three age groups, the urinary 8-OHdG of the younger group was higher than that of the older group using multiple regression analysis 3) . Yamamoto et al reported that the urinary 8-OHdG of subjects tended to decrease as their age increased 19) , but other studies have reported no significant results about age 2,7,20,21) . In the present study, there were no significant correlations between age and the differences in 8-OHdG at the three different storage temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…In an epidemiological study, Kasai et al reported that when subjects were divided into three age groups, the urinary 8-OHdG of the younger group was higher than that of the older group using multiple regression analysis 3) . Yamamoto et al reported that the urinary 8-OHdG of subjects tended to decrease as their age increased 19) , but other studies have reported no significant results about age 2,7,20,21) . In the present study, there were no significant correlations between age and the differences in 8-OHdG at the three different storage temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates a 50% increased rate of oxidative DNA damage from smoking, in addition to the other wellknown health hazards of smoking [11]. The urinary 8OHdG levels are also significantly higher in patients with gynecologic cancer, lung cancer and colorectal cancer, brain tumor than that in control subjects [12,13].…”
Section: Introductionmentioning
confidence: 93%
“…Toyokuni et al reported that human carcinoma cells (breast, lung, liver, kidney, brain, stomach, ovary) have a higher content of 8-OHdG than adjacent nontumorous tissues (11). Moreover, investigators have reported a high concentration of 8-OHdG in urine samples from patients with carcinoma of female genitalia (12), malignant breast tissues with invasive ductal carcinoma (10), colorectal tumor tissues (13), gastric cancer tissues (14), and lung cancer tissues (15). They hypothesized that the tumor cells themselves produce reactive oxygen species spontaneously resulting in an increase of 8-OHdG in DNA.…”
Section: Introductionmentioning
confidence: 99%